Organisational climate: variance across functional units - Van der Merwe, Izak Petrus (Department of Psychology, 2016)
The main objective of this research was to determine whether functional units (departments) in an industrial organization differed significantly with respect to their experience of the organizational climate. Two approaches to organizational theory were drawn from, namely, the systems and contingency approaches. Both emphasize the importance of the task environment and the need for the organization to adapt to its task environment. Systems theorists, Katz and Kahn (1978), have identified a number of organizational components or subsystems which enable the organization to function efficiently. Each component has a fairly specialized function; each develops a distinctive nucleus of operating procedures and values. Contingency theorists, Lawrence and Lorsch (1967, 1969), stated that different parts of the organization face different environments. Organizations therefore tend to become internally segmented into functional units. Organizational climate was highlighted as the general notion specifying the organizational identity or self-awareness of the organization; however, it may vary within the organization from work group to work group. The total number of 54 white employees in four units: marketing, personnel/public affairs, finance and production, at all levels - general employees, supervisory/foremen, middle management, senior management - completed a measure of their perceptions of the organizational climate of their individual units. The Organizational Climate Index for Profit Organizations developed by De Cock, Bouwen, de Witte and de Visch (1984), was used. The scale requires a forced choice on a scale with a scoring pattern of 4,3,2,1. Total scores on each of the 6 climate scales, grouped into 20 subscales, were obtained for each functional unit. One-way analysis of variance (the Kruskal-Wallis Test) was used for assessing the significance of differences between the four units on the different climate subscales. The results of the study supported the hypothesis that had been formulated. It was concluded that significant differences exist between the functional units marketing, personnel/public affairs, finance and production of the industrial organization concerned, with respect to the climate dimensions. It was concluded that, in order to achieve maximum integration between functional units and their members in an organization, business will need to concern itself with the differences in expression of human behaviour and motivation in units.